(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Leadership styles, especially transformational and transactional leadership, play an important role in the public sector by influencing organizational performance. This systematic literature review examines the effectiveness of these leadership styles in promoting organizational sustainability in the public sector. Following PRISMA guidelines, this study synthesizes findings from leading international databases, highlighting their impact on employee satisfaction, innovative behavior and organizational culture. The integration of transformational and transactional elements is explored for its potential to optimize organizational performance and enhance sustainability.